Threat of Hypercholesterolemia in Urban Adults and Its Associates: Evidence from a Community-Based Study - Yadav, Ambika Rani; Keshari, Priya (Makara Journal of Health Research, 2024)
Background: Hypercholesterolemia is an abnormality of lipids. It is a crucial modifiable risk factor for cardiovascular diseases. There is a paucity of community-based studies on hypercholesterolemia in the adult population in India. Given this context, the study aims to assess the prevalence and spectrum of hypercholesterolemia, along with its associated factors, among adult residents of urban areas in Prayagraj district, Uttar Pradesh, India. Methods: This community-based cross-sectional study was done on 536 urban adult subjects (30 to 59 years) of Prayagraj, India, selected by multistage sampling procedure. The predesigned and pretested interview schedule was used to obtain socio-demographic information about subjects. Nutritional parameters and serum cholesterol were assessed using the standard procedure. Statistical analysis was done using the Statistical Package for Social Sciences. The chi-square test and logistic regression analysis were done for association and inferential purposes, respectively. Results: The prevalence of Hypercholesterolemia was 24.4%. This was significantly (p < 0.05) higher in subjects aged 50-59 years, family size 2-4, and having higher body mass index, waist circumference, and visceral fat%. Age emerged as a significant predictor of hypercholesterolemia. Conclusions: One out of 4 urban subjects had hypercholesterolemia. This study emphasizes the need for age-specific screening and preventive and promotive services to reduce hypercholesterolemia.